Young adolescent cancer survivors and their parents: adjustment, learning problems and gender. - Kazak, Anne E.; Christakis, Dimitri; Alderfer, Melissa (Journal of Family Psychology, 1994)
This study investigated adjustment in 10–15-year-old long-term survivors of childhood cancer and their parents (N = 59) at two points 1 year apart. Behavioral concerns, parental distress, anxiety, hopelessness, social support, and family functioning were assessed. Gender and the presence of learning problems were examined. The data indicated levels of adjustment that were near normative levels. However, gender differences were found, with male adolescents reporting low levels of anxiety and hopelessness. Those survivors with learning difficulties appeared particularly vulnerable with respect to long-term adjustment. Reprinted by permission of the publisher.